Chemical Characteristics of Inceptisol Soil With Urea and Goat Manure Fertilizer - Fitra Syawal Harahap; Roswita Oesman; Wizni Fadhillah; Mulya Rafika (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2021)
The application of organic fertilizers can improve soil fertility specifically on Inceptisol soils which are quite extensive but have problems with relatively low nitrogen nutrients so that the effort to overcome this is through the addition of organic matter into the soil through organic fertilization or with inorganic fertilizers. The purpose of this study was to determine the effect of the application of goat and urea fertilizer on the chemical properties of inceptisols from Rantau Selatan. This research was carried out at the Agrotechnology Practice Field, Faculty of Science and Technology, Labuhanbatu Rantau Prapat University from February to May 2021. This study used a factorial Randomized Block Design (RAK) with 2 factors, namely factor 1 urea with 4 levels, namely: U0 = 100 kg urea /ha (0 g urea/5 kg weight of oven-dry soil or BTKO), U1= 100 kg urea/ha (0.25 g urea/5 kg BTKO), U2= 200 kg urea/ha (0.50 g urea/ha) 5 kg BTKO), U3 = 300 kg urea/ha (0.75 g urea/5 kg BTKO) and factor 2, the factor of giving goat manure with 3 levels, namely: K0 = 0 tons N/ha (0 goat manure/ 5 kg of oven-dry soil weight), K1 = 10 tons N/ha (25 g Fertilizer, Goat Cage/5 kg BTKO), K2 = 20 tons N/ha (50 g Fertilizer, Goat Cage/5 kg BTKO), K3 = 30 tons N/ha (75 g Fertilizer, Goat Cage/5 kg BTKO). The results of the research application of goat manure increased the N-total dose of Urea: 0.25g and goat manure: 75g on Inceptisol soil while the interaction of urea and goat manure application increased the total N-total with Urea dose: 0.25g and goat manure: 75g) South Coast Inceptisol soil